Immune-checkpoint targeting drug conjugates: a novel class of promising therapeutic agents for cancer treatment - Silvia Marchesi; Arianna Marinello; Paolo Ambrosini; Chiara Cavalli; Giuseppe Lo Russo; Mario Occhipinti (npj Precision Oncology)
Abstract Immune-checkpoint targeting Drug Conjugates (IDCs) are a novel class of therapeutics that combine an immune checkpoint-targeting moiety, a cleavable linker, and a cytotoxic payload. By integrating features and functions of antibody-drug conjugates and immunotherapy, IDCs represent a promising strategy to remodel the tumor microenvironment and enhance antitumor efficacy. Several IDCs targeting checkpoints such as PD-L1, B7-H3, and B7-H4 are in early-phase clinical trials. This review summarizes available data on IDC efficacy and toxicity in human. Although current evidence is limited, ongoing phase III trials and biomarker studies will clarify their optimal clinical role, including potential for tumor-agnostic use.